Pelabelan Produk dan Merek Dagang untuk Promosi Penjualan pada Warung Armina Karang Pule - Phyta Rahima; Suriyati Suriyati; Hilda Hastuti (LPPM Universitas Bumigora, 2022)
The development of home-based businesses in Indonesia is very fast, especially in areas such as the island of Lombok. Most of the people depend on the economy from the results of selling, ranging from selling clothes, toys and household furniture, but in the city of Mataram itself, it is already crowded with home-based food businesses whose activists are housewives who want to increase pocket money or monthly money and look for busy activities. Later it is expected to be able to bring in income which is considered capable of increasing household economic income. The business that is currently booming is the Geprek chicken business which can be easily found along the streets of Mataram City. Geprek chicken business itself is a business that is classified as very easy to do because its composition only consists of chicken coated with crispy flour, added with rice and cucumber vegetables and geprek chili sauce. It is very popular with the public because 1 package of geprek chicken is only valued at Rp. 10,000, - and that includes Ice Tea. Meanwhile, the partner in this service is Warung Armina. Warung Armina is a geprek chicken stall located in the Karang Pule neighborhood of Mataram City. Warung Armina not only sells geprek chicken but also nasi padang, kebuli rice and mixed rice, so this is what sets it apart from other geprek chicken stalls. In the development of its business, Warung Armina is only run by a husband and wife who rely on neighbors and motorcyclists who pass in front of the house so that this becomes an attraction for our team to do service to the Armina stall until we get the right model for labeling and packaging. The activities were carried out by observing, interviewing and having direct dialogue with the shop owners about the wishes and obstacles they faced. With a comfortable dialogue, the expected final result is the right label and promotion for armina stalls up to the registration of Armina stalls at Grabfood Merchant and Gofood Merchant.